Modelagem de controle do inversor para geração distribuída em DIgSILENT PowerFactory® para análise de redes elétricas - Silva, Igleyce Kelly Alves da (2019)
This work presents the inverter control modeling in DIgSILENT PowerFactory® to analyze the effects of distributed generation sources (DG) in the network. The modeling of this inverter was designed considering the "Composite Model" block, which consists of slots, to which controllers or predefined elements can be assigned ('Common Models'), within a dynamic system. Thus, the use of this tool allows a very detailed analysis of the dynamic behavior of the system, allowing the control of its variables. To apply to a large system, the design of controllers for a grid was entirely carried out, and then it was implemented in a 9-bus system. Short circuit and load switching analyzes were performed and the numerical results are presented and discussed to demonstrate the applicability of the proposed inverter control modeling in large systems